Changes in systemic GDF15 across the adult lifespan and their impact on maximal muscle power: the Copenhagen Sarcopenia Study. Issue 6 (6th October 2021) - Alcazar, Julian; Frandsen, Ulrik; Prokhorova, Tatyana; Kamper, Rikke S.; Haddock, Bryan; Aagaard, Per; Suetta, Charlotte
Abstract: Background: Although growth differentiation factor 15 (GDF15) is known to increase with disease and is associated with low physical performance, the role of GDF15 in normal ageing is still not fully understood. Specifically, the influence of circulating GDF15 on impairments in maximal muscle power (a major contributor to functional limitations) and the underlying components has not been investigated. Methods: Data from 1305 healthy women and men aged 20 to 93 years from The Copenhagen Sarcopenia Study were analysed. Circulating levels of GDF15 and markers of inflammation (tumor necrosis factor‐alpha, interleukin‐6, and high‐sensitivity C‐reactive protein) were measured by ELISA (R&D Systems) and multiplex bead‐based immunoassays (Bio‐Rad). Relative (normalized to body mass), allometric (normalized to height squared), and specific (normalized to leg muscle mass) muscle power were assessed by the Nottingham power rig [leg extension power (LEP)] and the 30 s sit‐to‐stand (STS) muscle power test. Total body fat, visceral fat, and leg lean mass were assessed by dual energy X‐ray absorptiometry. Leg skeletal muscle index was measured as leg lean mass normalized to body height squared. Results: Systemic levels of GDF15 increased progressively as a function of age in women (1.1 ± 0.4 pg·mL −1 ·year −1 ) and men (3.3 ± 0.6 pg·mL −1 ·year −1 ) (both P < 0.05). Notably, GDF15 increased at a faster rate from the age of 65 years in women (11.5 ± 1.2 pg·mL −1 ·year −1, P < 0.05) and 70 years in men (19.3 ± 2.3 pg·mL −1 ·year −1, P < 0.05), resulting in higher GDF15 levels in men compared with women above the age of 65 years ( P < 0.05). Independently of age and circulatory markers of inflammation, GDF15 was negatively correlated to relative STS power ( P < 0.05) but not LEP, in both women and men. These findings were mainly explained by negative associations of GDF15 with specific STS power in women and men (both P < 0.05). Conclusions: A J‐shaped relationship between age and systemic GDF15 was observed, with men at older age showing steeper increases and elevated GDF15 levels compared with women. Importantly, circulating GDF15 was independently and negatively associated with relative STS power, supporting the potential role of GDF15 as a sensitive biomarker of frailty in older people.